2019
DOI: 10.1111/1365-2478.12793
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid optimization scheme for self‐potential measurements due to multiple sheet‐like bodies in arbitrary 2D resistivity distributions

Abstract: Self‐potential is a passive geophysical method that can be applied in a straightforward manner with minimum requirements in the field. Nonetheless, interpretation of self‐potential data is particularly challenging due to the inherited non‐uniqueness present in all potential methods. Incorporating information regarding the target of interest can facilitate interpretation and increase the reliability of the final output. In the current paper, a novel method for detecting multiple sheet‐like targets is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…The procedure based on interpretation of self-potential anomalies due to simple geometrical structures using Fair function minimization (Tlas and Asfahani, 2013), is of certain interest. Giannakis et al (2019) suggested a hybrid optimization scheme for SP measurements due to multiple sheet-like bodies. This procedure demands a wide verification on concrete field examples.…”
Section: Review Of Quantitative Interpretation Methodsmentioning
confidence: 99%
“…The procedure based on interpretation of self-potential anomalies due to simple geometrical structures using Fair function minimization (Tlas and Asfahani, 2013), is of certain interest. Giannakis et al (2019) suggested a hybrid optimization scheme for SP measurements due to multiple sheet-like bodies. This procedure demands a wide verification on concrete field examples.…”
Section: Review Of Quantitative Interpretation Methodsmentioning
confidence: 99%
“…A poor choice of the initial point may lead to suboptimal solutions, and the success of the algorithm is somewhat tied to the quality of the initial model. The present study addresses this challenge by introducing a methodology that integrates genetic algorithms and pattern search [38][39][40][41][42][43][44]. The approach involves providing a limited time for the genetic algorithm to obtain near-optimal results.…”
Section: Hybrid Optimizationsmentioning
confidence: 99%